Spectral Analysis on Medial Axis of 2D Shapes. (13th June 2014) - He, Shuiqing; Choi, Yi‐King; Guo, Yanwen; Wang, Wenping
<x xml:space="preserve">Abstract</x> Shape analysis finds many important applications in shape understanding, matching and retrieval. Among the various shape analysis methods, spectral shape analysis aims to study the spectrum of the Laplace‐Beltrami operator of some well‐designed shape dependent equations and obtain a spectral shape descriptor that can in turn be used for shape analysis purposes. The success of such approaches depends greatly on the discriminating power of a shape descriptor. On the other hand, the medial axis of a shape is widely known for its complete shape representation. It is sensitive to small perturbation of the boundary of a shape which often poses difficulty in its effective use for shape analysis. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>